Penta-o-galloyl-beta-d-Glucose (PGG) inhibits inflammation in human rheumatoid arthritis synovial fibroblasts and rat adjuvant-induced arthritis model - Umar, Sadiq; Singh, Anil K.; Chourasia, Mukesh; Rasmussen, Stephanie M.; Ruth, Jeffrey H.; Ahmed, Salahuddin (Frontiers in Immunology, 2022)
O-GlcNAcylation is a reversible post-translational modiﬁcation that regulates numerous cellular processes, including embryonic development as well as immune responses. However, its role in inﬂammation remains ambiguous. This study was designed to examine the role of O-GlcNAcylation in rheumatoid arthritis (RA) and its regulation using human RA patient-derived synovial fibroblasts (RASFs). The efficacy of penta-O-galloyl-beta-D-glucose (PGG), a potent anti-inflammatory molecule, in regulating inflammatory processes in human RASFs was also evaluated. Human synovial tissues and RASFs exhibited higher expression of O-GlcNAcylation compared to their non-diseased counterparts. Pretreatment of RASFs with Thiamet G, an inhibitor of O-GlcNAcase, markedly increased the O-GlcNAc-modified proteins and concomitantly inhibited the IL-1β-induced IL-6 and IL-8 production in human RASFs in vitro. Pretreatment of human RASFs with PGG (0.5-10 µM) abrogated IL-1β-induced IL-6 and IL-8 production in a dose-dependent manner. Immunoprecipitation analysis showed that PGG inhibited O-GlcNAcylation of TAB1 to reduce its association with TGF β-activated kinase 1 (TAK1) and its autophosphorylation, an essential signaling step in IL-1β-induced signaling pathways. Molecular docking in silico studies shows that PGG occupies the C174 position, an ATP-binding site in the kinase domain to inhibit TAK1 kinase activity. Oral administration of PGG (25 mg/kg/day) for 10 days from disease onset significantly ameliorated rat adjuvant-induced (AIA) in rats. PGG treatment reduced the phosphorylation of TAK1 in the treated joints compared to AIA joints, which correlated with the reduced disease severity and suppressed levels of serum IL-1β, GM-CSF, TNF-α, and RANKL. These findings suggest O-GlucNAcylation as a potential therapeutic target and provide the rationale for testing PGG or structurally similar molecule for their therapeutic efficacy.